Social determinants of residential electricity consumption in Korea: Findings from a spatial panel model. (15th January 2022) - Park, Jongmun; Yun, Sun-Jin
Abstract: Residential electricity consumption is steadily increasing in Korea, whose carbon emissions from fuel combustion are ranked 7th globally. However, various social variables that affect electricity demand have changed in recent years, and there are many differences in local distribution. This study analyzed electricity consumption factors in 225 Korean municipalities from 2010 to 2019, using a spatial panel model to reflect local characteristics and temporal differences in social variables. The study found that spatial interactions of residential electricity consumption in the metropolitan area and consumption among adjacent areas showed similar patterns. The social determinants such as household sizes, marriage, apartment were found to affect electricity consumption. The interaction effect shows the effects of aging and apartments in more detail. The spatial interaction effect on electricity consumption at home suggests that innovative policies to promote an eco-lifestyle can have spillover effects around metropolitan areas. Given the increase in single-person households, the spread of apartments, and the increase in the elderly population with purchasing power, those variables should be defined as the targets for managing residential electricity demand. Highlights: Residential electricity consumption is clustered mainly in the metropolitan area. The effect of spatial autocorrelation is confirmed by using a spatial panel model. Recent social structure and housing trends are significant social determinants. Innovative initiatives and multi-level interaction are important for energy-saving.